Analysis Of Risk Factors For Delay In Emergency Handling In Primary Services - Br. Tarigan, Junita (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Delays in the treatment of unidentified accident victims can increase the risk of complications and death, especially in cases of severe trauma. Therefore, it is essential to identify the factors contributing to these delays.This study employs a qualitative approach with a descriptive method, involving 10 informants selected based on their experience in handling unidentified patients during the research period. A purposive sampling technique was applied to choose informants who met the study's relevant criteria.The research instrument used was a semi-structured interview guide with open-ended questions designed to explore the informants' experiences and perspectives regarding delays in treating unidentified patients.The findings reveal several key factors causing these delays, such as ineffective coordination with the police and a lack of necessary information for the identification process. These factors are interconnected and impact the quality of care provided to the victims.To minimize delays, hospitals are advised to strengthen inter-agency cooperation, utilize digital technology to expedite identification, and provide continuous training for medical and administrative staff. These steps are expected to improve the quality of services in handling unidentified accident victims.